Prerequisites for high-quality official control in Finnish slaughterhouses. (September 2017) - Luukkanen, Jenni; Fredriksson-Ahomaa, Maria; Nevas, Mari; Lundén, Janne
Abstract: To ensure the safety of meat, official control, including meat and food safety inspections in slaughterhouses, should be of high quality. The prerequisites for high-quality official control were examined by sending a questionnaire to meat inspection personnel, slaughterhouse representatives, and officials who guide and organize the official control of slaughterhouses at the central level in Finland. The questionnaire inquired about the sufficiency of meat inspection personnel resources and its effects on official control. The post-mortem inspection skills of the official auxiliaries (OAs) and steps taken by the official veterinarians (OV) to evaluate OAs' performance in post-mortem inspection were explored. Furthermore, OAs' independence from the slaughterhouses in meat inspection, and further training and guidance provided to meat inspection personnel were surveyed. Our results showed that in most slaughterhouses at least occasional shortage of OVs was experienced, and it decreased especially the time dedicated to food safety inspections, meat inspection personnel's participation in further training, and guidance given to OAs by OVs. All but one chief OV considered the skills of the regular OAs in post-mortem inspection to be totally sufficient, whereas over a third of the chief OVs did not find the post-mortem inspection skills of the OA substitutes totally sufficient. In red meat slaughterhouses, the frequency of the observation of the post-mortem inspection performed by the OAs was variable, and one-third of the red meat OAs considered that their performance in post-mortem inspection was not sufficiently evaluated by the OVs. Although most of the meat inspection personnel agreed that OAs understand working independently from the slaughterhouse in meat inspection, a substantial number of poultry OAs in particular stated that the independency was not entirely clear to them. A majority of the chief OVs considered that the officials guiding meat and food safety inspections at the central level are unaware of the practical problems involved in OVs' work. Our results highlight the importance of practical experience for the officials guiding the official control in slaughterhouses and increased feedback between OVs and OAs in slaughterhouses. An adequate number of OVs should be guaranteed in all slaughterhouses. The practices to evaluate the red meat OAs' performance in post-mortem inspection should be standardized and the maintenance of the post-mortem inspection skills of OA substitutes improved. Highlights: Shortage of official veterinarians (OVs) occurred in most slaughterhouses. Official auxiliary (OA) substitutes' meat inspection skills should be improved. Frequency of the observation of red meat OAs' performance varied markedly. OVs should invest in guiding red meat OAs in post-mortem inspection. Most OVs required further training related to application of legislation.